2006
DOI: 10.2174/092986706776360905
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry and Biology of Chromatin Remodeling Agents: State of Art and Future Perspectives of HDAC Inhibitors

Abstract: Chromatin remodeling is a fundamental phenomenon in the life of eukaryotic cells, bearing implications to numerous physiological and pathological phenomena. This review outlines the chemistry of natural and synthetic agents endowed with the ability to interfere with such biological function, with a particular emphasis on histone deacetylase (HDAC) inhibitors. Other aspects covered in this article comprise structure activity relationships (SAR) and modes of action at molecular level, including the description o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
74
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(75 citation statements)
references
References 80 publications
0
74
0
1
Order By: Relevance
“…Inhibition of HDAC activity therefore has the effect of promoting the transcription of silenced genes. Application of HDAC inhibitors in cancer cell lines and mouse model systems leads to interruption of the cell cycle, differentiation, and apoptosis [3][4][5][6]. Clinical studies have shown tumor repression and improvement of patient symptoms without significant side effects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibition of HDAC activity therefore has the effect of promoting the transcription of silenced genes. Application of HDAC inhibitors in cancer cell lines and mouse model systems leads to interruption of the cell cycle, differentiation, and apoptosis [3][4][5][6]. Clinical studies have shown tumor repression and improvement of patient symptoms without significant side effects.…”
Section: Introductionmentioning
confidence: 99%
“…Investigations of other short chain acids, such as 4-phenylbutyric acid and valproic acid (Figure 1), have shown them to be effective against similar cancer cell lines [16,17]. Although 4-phenylbutyric acid's in vitro efficacy is low, it was the first HDAC inhibitor to be evaluated in clinical trials [3]. Valproic acid, a drug currently used to treat epilepsy and bipolar disorder, has a significantly longer half-life than sodium butyrate and has an established clinical record [16].…”
Section: Introductionmentioning
confidence: 99%
“…Hyperacetylation [2,24,25] results in an increase in the space between the nucleosome and the DNA that is wrapped around it. The opening of chromatin structure subsequently provides the access for gene transcription.…”
Section: Hdac6 Inhibitormentioning
confidence: 99%
“…[2] Inhibitors of HDACs regulate gene transcription through hyperacetylation of nucleosomal histone and non-histone proteins. [24,25] HDACIs also have effects on non-histone proteins which include proteins involved in the regulation of gene expression, pathways of extrinsic and intrinsic apoptosis, cell-cycle progression, redox pathways, mitotic division, DNA repair, cell migration and angiogenesis. [2,[33][34][35][36][37][38][39] In general, amplified levels of histone acetylation lead to de-condensation of chromatin allowing DNA accessible to transcription factors, and are thus related with increased transcriptional activity, whereas decreased acetylation levels are associated with transcriptional repression.…”
Section: Hdac6 Inhibitormentioning
confidence: 99%
“…VA has been used at concentrations approaching 1 mM in vitro [47], doses that are impossible to achieve clinically. HDAC inhibitors with activity in the nanomolar range have been reported [48] and these might be useful in obtaining maximal benefit from a purging strategy. …”
Section: Clinical Attempts At Purging Latent Hiv-1 Reservoirsmentioning
confidence: 99%